(untitled) (Research, Society and Development, 2024)
Objective: to carry out a comprehensive epidemiological survey of patients undergoing cardiovascular surgery in the city of Parnaíba. We sought to analyze and understand the incidence, demographic distribution and risk factors associated with these surgical interventions, aiming to contribute to the improvement of clinical practices and local health policies. Methodology: The research was conducted through a comprehensive literature review, considering previous studies on cardiovascular surgeries, cardiovascular epidemiology and health indicators. Furthermore, data analysis was carried out from Datasus, using information compiled from hospital records. Results: The results include a detailed description of the incidence of cardiovascular surgeries in the region, highlighting demographic characteristics, such as age group and gender. It also identified possible predominant risk factors and their relationship between cardiovascular surgeries and underlying health conditions. The literature review provided broad context, while Datasus data added a specific local perspective. Conclusion: the conclusions of this study provide support for improving health policies aimed at prevention, early diagnosis and effective treatment of cardiovascular diseases in Parnaíba. Furthermore, this epidemiological survey contributes to the development of strategies aimed at specific risk groups, promoting improved quality of life and reducing the burden of cardiovascular diseases in the studied community.